Feed Adaptation by Using Leucaena leucocephala as a Replacement of Soybean Flour For Osphronemus gourami Feed - Muhammad Amri; Siti Aisyah; Ermi Husni (Fakultas Perikanan dan Kelautan, Universitas Riau, 2023)
One type of legume that is very suitable to be used as a raw material for making Osphronemus gourami feed is the Lamtoro gung leaves (Leucaena leucocephala). Soybeans which are a source of vegetable protein can now be supported by sword beans. The purpose of this study was to examine the quality of artificial feed using Lamtoro gung leaves (Leucaena leucocephala) as a substitute for soybean flour for Osphronemus gourami feed. The method used is the experimental method with RAL using 4 treatments and 3 replications. The treatments in this study were A (artificial feed without Lamtoro gung leaves (control)), B (2.5% Lamtoro gung leaves in 1 kg artificial feed), C (3% Lamtoro gung leaves in 1 kg artificial feed), and D ( 3.5% Lamtoro gung leaves in 1 kg of artificial feed). Research data were analyzed using non-parametric Kruskal Wallis statistical test and described. The test animal used was the Osphronemus gourami with a size of 8-10 cm with an average weight of 200-300 grams. The results of the physical test showed that the parameters of breaking speed, level of hardness, level of homogeneity and attractiveness were significantly different from the use of Lamtoro gung leaves flour, while the parameters of sinking speed and deliciousness were not significantly different. The results of the proximate chemical test of feed using the best swordfish flour was in feed B, which contained 9.34% Moisture Content, 11.87% Ash Content, Crude Protein (N x 6.25) 29.98%, Crude Fat 6, 84 %, Carbohydrates 39,65% and Crude Fiber 7,13 %.